Investigation of the relation between symptom characteristics and drug use in patients who have been living abroad and referred to psychiatry outpatient clinic during their military process - Özdemir, Barbaros; Çelik, Cemil; Doruk, Ali; Cüceloğlu, Aydın; Balıkçı, Adem; Özşahin, Aytekin (Journal of Dependence, 2009)
Objective: Emigration is an important social event that has psychosocial effects on individuals and carries on these effects for many generations. The aim of this study, we aimed to investigate the relationship between psychiatric symptom characteristics and substance use in cases who have emigrated to Europe from Turkey and referred to Gülhane Military Medical Faculty (GATF) Psychiatry Outpatient clinic.Method: Fifty-two cases who have been living at different European countries and referred toGATFpsychiatry outpatient clinic during their military process admitted to the study. The cases were evaluated by applying SCID-I and SCID-II. Symptom characteristics were examined by using the Brief Symptom Inventory (BSD.Results: Of the cases, 57.7 % had a history of substance abuse (n=30) and 42.3 % had not (n=22). By comparison of mean scores of BSI for sociodemographic findings there was not a statistically significant difference except substance users. Mean scores of BSI in substance users were significantly lesser than nonusers. This significance was more evident for comparison of scores between heroin and/or cocaine users with cases that have never used any substance.Conclusion: It was found that substance users have lesser symptom scores. The findings of this study doesn't support the hypothesis that puts forward a positive correlation between psychiatric symptom characterization and the intensity ofsubstance use at individuals that abuse various substances. Studies that are prospective, controlled, multi centered, transcultural and also that are evaluating cognitive functions should be planned on this issue.
Keywords: Substance use disorders; sociodemographic features; clinical features